1994
DOI: 10.1007/bf02352254
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of hip fractures in independent and institutionalized elderly people

Abstract: Abstract. The incidence density of hip fractures in the population of Amsterdam, aged 70 years and over, was studied according to the type of residence. In 1989, 655 patients were admitted to nine hospitals within Amsterdam for a hip fracture. Postal codes were used to classify the residence of the population and the hip fracture cases as independent, home for the elderly or nursing home. Stepwise logistic regression was used for data analysis. The risk of hip fracture increased with age and was 1.7 times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 14 publications
3
59
1
2
Order By: Relevance
“…The findings with respect to age and gender have also been reported in previous studies [6,9,13]. The high incidence of hip fractures in residents of homes for the elderly (25.5 per 1000 person-years) compared with the total population confirms previous results in the population of Amsterdam [14]. Other fractures, not of the hip or distal forearm, were related to gender only.…”
Section: Discussionsupporting
confidence: 89%
“…The findings with respect to age and gender have also been reported in previous studies [6,9,13]. The high incidence of hip fractures in residents of homes for the elderly (25.5 per 1000 person-years) compared with the total population confirms previous results in the population of Amsterdam [14]. Other fractures, not of the hip or distal forearm, were related to gender only.…”
Section: Discussionsupporting
confidence: 89%
“…In 2012, LTC residents had up to double the relative risk for hip fractures, which is lower than what was reported in older studies [24][25][26][27]. Older studies reported the highest risk ratios in the youngest senior age strata [15,25]. For the LTC cohort, our incidence rates were similar to [15,27,28] or lower than [29,30] other published studies on institutionalized populations, particularly Chandler et al who reported a rate of 109 osteoporotic fractures per 1000 person-years [31].…”
Section: Discussioncontrasting
confidence: 41%
“…For hip fractures, our age-adjusted risk ratios for LTC versus community residents were similar to those reported by Crilly et al [15] for women and lower for men. In 2012, LTC residents had up to double the relative risk for hip fractures, which is lower than what was reported in older studies [24][25][26][27]. Older studies reported the highest risk ratios in the youngest senior age strata [15,25].…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, application of hip protectors in nursing homes by staff may be considered an important cointervention, not available in other group residence settings; this issue could be another contributor to clinical heterogeneity of pooled analyses of mixed populations. The nursing home population was of greatest clinical interest, as this population is known to be at extremely high risk for osteoporosis [14][15][16], falls [17], cognitive impairment (leading to falls and hip fracture) [16], and hip fracture [18][19][20].…”
Section: Selection Of Trials For Inclusion and Data Abstractionmentioning
confidence: 99%